2014
DOI: 10.1111/ina.12152
|View full text |Cite
|
Sign up to set email alerts
|

Contaminant levels, source strengths, and ventilation rates in California retail stores

Abstract: Field measurements suggest that California retail stores were well ventilated relative to the minimum ventilation rate requirement specified in the Building Energy Efficiency Standards Title 24. Concentrations of formaldehyde found in retail stores were low relative to levels found in homes but exceeded the most stringent chronic health guideline. Looking ahead, California is mandating zero energy commercial buildings by 2030. To reduce the energy use from building ventilation while maintaining or even lowerin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 14 publications
(20 reference statements)
2
25
0
Order By: Relevance
“…Aside from the two contaminants considered here, there were other differences in contaminant concentrations between grocery stores and other retail store types. Concentrations of acetaldehyde and d‐limonene were about two times higher in grocery stores compared to the other store types (Chan et al., ). The mean indoor acetaldehyde concentration of 19 μ g/m 3 measured in grocery stores exceeded the U.S. EPA RfC of 9 μ g/m 3 , but it was below OEHHA chronic REL of 140 μ g/m 3 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Aside from the two contaminants considered here, there were other differences in contaminant concentrations between grocery stores and other retail store types. Concentrations of acetaldehyde and d‐limonene were about two times higher in grocery stores compared to the other store types (Chan et al., ). The mean indoor acetaldehyde concentration of 19 μ g/m 3 measured in grocery stores exceeded the U.S. EPA RfC of 9 μ g/m 3 , but it was below OEHHA chronic REL of 140 μ g/m 3 .…”
Section: Discussionmentioning
confidence: 99%
“…This half‐life is sufficiently longer than the time constant associated with the average building ventilation rate of 1/h measured in the grocery and retail stores (see Chan et al. () for values of measured ventilation rates), corresponding to a half‐life of 0.7 h. Thus, for the purpose of calculating the indoor emission source strength, we assumed that there was negligible removal of acrolein other than by ventilation.E=false(CinCoutfalse)×koa×V…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most buildings in the Bennett et al [8] study did not meet California's Title 24 minimum requirements for ventilation on a per area basis. Chan et al (2012Chan et al ( , 2014) conducted a study of retail stores in California, which showed that HCHO concentrations exceeded the OEHHA REL, and that acetaldehyde and acrolein levels exceeded the reference concentration for chronic inhalation exposure (RfC) issued by the U.S. EPA [10] while meeting or exceeding the Title 24 minimum ventilation requirement of 7 L/s person or 1 L/s m 2 . The highest levels of HCHO were measured in apparel stores, and acetaldehyde and acrolein were highest in grocery stores.…”
Section: Introductionmentioning
confidence: 99%